Landscapes of warfare: Urartu and Assyria in the ancient Middle East - Earley-Spadoni, Tiffany, author; University Press of Colorado, publisher (Colorado State University. Libraries, 2025)
Landscapes of Warfare analyzes the ancient polity of Urartu, linking the development of ideology and technology between Urartu and Assyria to wider historical continuities, particularly related to warfare.--Provided by publisher.
Landscapes of Warfare: A Historiography -- Age of Empires: An Introduction to the Early First Millennium BCE -- Views from the Fortress: Examining Site Placement -- Reframing Urartu as a Non-Urban Empire -- Fortified Regional Networks (FRN): Building Blocks of Empire -- Movement and Mobility: the Space of Empire -- Traumascapes: War and Society Writ Large -- Unraveling the Why: Ideologies that Perpetuate Landscapes of War.
Keywords: Landscapes -- Urartu -- History; Landscape archaeology -- Urartu; Urartu -- History; Assyria -- History; Urartu -- History, Military